Sea-Level Rise Exposure and Municipal Bond Yields - Goldsmith-Pinkham, Paul; Gustafson, Matthew T; Lewis, Ryan C; Schwert, Michael (Review of Financial Studies, 2023)
Municipal bond markets began pricing sea-level rise (SLR) exposure risk in 2013, coinciding with upward revisions to worst-case SLR projections and accompanying uncertainty around these projections. The effect is larger for long-maturity bonds and not solely driven by near-term flood risk. We use a structural model of credit risk to quantify the implied economic impact and distinguish between the effects of underlying asset values and of uncertainty. The SLR exposure premium exhibits a trend different from house prices and is unaffected by house price controls. Together, our results highlight the importance of climate uncertainty in driving municipal bond prices. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online